2015
DOI: 10.1681/asn.2014040354
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers for PKD1 Using Urinary Exosomes

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a common cause of ESRD. Affected individuals inherit a defective copy of either PKD1 or PKD2, which encode polycystin-1 (PC1) or polycystin-2 (PC2), respectively. PC1 and PC2 are secreted on urinary exosome-like vesicles (ELVs) (100-nm diameter vesicles), in which PC1 is present in a cleaved form and may be complexed with PC2. Here, label-free quantitative proteomic studies of urine ELVs in an initial discovery cohort (13 individuals with PKD1 mutations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 32 publications
2
103
0
Order By: Relevance
“…This suggests possible diseasespecific modifications. Recently, Hogan et al 92 showed that transmembrane protein-2 (TMEM2) in uEX was 2-fold higher in patients with PKD1 compared with controls. PC to TMEM ratio correlated inversely with kidney volume.…”
Section: Tubular Diseasementioning
confidence: 99%
“…This suggests possible diseasespecific modifications. Recently, Hogan et al 92 showed that transmembrane protein-2 (TMEM2) in uEX was 2-fold higher in patients with PKD1 compared with controls. PC to TMEM ratio correlated inversely with kidney volume.…”
Section: Tubular Diseasementioning
confidence: 99%
“…To determine whether the ΔL mutation affects PC1 intracellular membrane localization we analyzed protein from E14.5 whole embryo membrane preparations following fractionation over a heavy water/5–30% sucrose gradient (35) to separate membrane compartments. Immunoblot analysis of the total membrane preparations revealed comparable levels of full-length, and mature and immature NTF glycoforms of PC1 from WT and Pkd1 ΔL/ΔL embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Membranes were clarified by gentle centrifugation, equilibrated and applied to a heavy water/5–30% sucrose gradient (35) and centrifuged at ∼274 000 g for 16 h in a Sorvall TH-641 rotor. Gradient fractions were collected from the top down using a BioComp fraction collector.…”
Section: Methodsmentioning
confidence: 99%
“…A tantalizing but untested possibility is that polycystin inactivation results in both abnormal ciliary EVs and abnormal ciliary signaling, resulting in severe pathology (scenerios shown in Figure 2C and 2D). The latter was previously demonstrated while the former only recently: EVs isolated from ADPKD patients display different proteins than unaffected individuals and hence the proposal that urinary exosomes contain biomarkers for ADPKD (Hogan et al, 2015). By removing the cilium in a Pkd1 or Pkd2 mutant, abnormal EV-cilia interactions and signaling are abrograted, thereby suppressing cystogenesis.…”
Section: Do Abnormal Cilia-ev Interactions Contribute To Ciliopathies?mentioning
confidence: 97%